Revenue Law in Singapore and Malaysia - Leo Desmond Pointon, Jeon Chun Phuoc (Lexis Nexis, 2012)
The shari'ah revenue law perspective will undoubtedly generate interest in other areas of shari'ah subject matters where tax is a factor.